Direct Crosstalk Between O-GlcNAcylation and Phosphorylation of Tau Protein Investigated by NMR Spectroscopy - Bourré, Gwendoline; Cantrelle, François-Xavier; Kamah, Amina; Chambraud, Béatrice; Landrieu, Isabelle; Smet-Nocca, Caroline (Frontiers in Endocrinology, 2018)
The formation of intraneuronal fibrillar inclusions of tau protein is associated with several neurodegenerative diseases referred to as tauopathies including Alzheimer’s disease (AD). A common feature of these pathologies is hyperphosphorylation of tau, the main component of fibrillar assemblies such as Paired Helical Filaments (PHFs). O-β-linked N-acetylglucosaminylation (O-GlcNAcylation) is another important posttranslational modification involved in regulation of tau pathophysiology. Among the benefits of O-GlcNAcylation, modulation of tau phosphorylation levels and inhibition of tau aggregation properties have been described while decreased O-GlcNAcylation could be involved in the raise of tau phosphorylation associated with AD. However, the molecular mechanisms at the basis of these observations remain to be defined. In this study, we identify by NMR spectroscopy O-GlcNAc sites in the longest isoform of tau and investigate the direct role of O-GlcNAcylation on tau phosphorylation and conversely, the role of phosphorylation on tau O-GlcNAcylation. We show here by a systematic examination of the quantitative modification patterns by NMR spectroscopy that O-GlcNAcylation does not modify phosphorylation of tau by the kinase activity of ERK2 or a rat brain extract while phosphorylation slightly increases tau O-GlcNAcylation by OGT. Our data suggest that indirect mechanisms act in the reciprocal regulation of tau phosphorylation and O-GlcNAcylation in vivo involving regulation of the enzymes responsible of phosphate and O-GlcNAc dynamics.